‘Where there are people, there is trade’ retail location pattern and shop architecture in Amsterdam, c. 1550–1850 (Bulletin KNOB, 2015)
This essay provides an overview of the evolution of the location and appearance of Amsterdam shops in the period from around 1550 to 1850. With the aid of a new technique (Space Syntax Analysis) it has been established that shops selling luxury goods were located in highly accessible areas within the Amsterdam street network. In practice this meant in the vicinity of Dam Square, the old riverbanks either side of the River Amstel, and along the radial streets running from the city gates and outlying districts into the city centre. Because the street pattern of the early modern part of Amsterdam changed very little, existing accessibility patterns and thus also the retail function of the old shopping streets endured. Even today those old retail development patterns are still apparent. Shops selling food and other daily necessities were – in line with existing location theories – dispersed across the city.For centuries Amsterdam shops had an open character reminiscent of market stalls. Shopkeepers placed their wares on the stoop, on window ledges and on folded-down lower shutters, or they hung the goods from the well-nigh ubiquitous awnings. This practice was hardly surprising since the front part of the house was usually poorly lit, and steps, cellar doors, cellar shops and other obstacles prevented pedestrians from walking close to the facades. As such, the facade and the stoop served as the shopkeeper’s display case. It was not until the late seventeenth century and more especially during the eighteenth century that the shops on the main shopping streets started to place their wares inside the building, thereby following the example of shops in London and Paris and responding to the welltodo clientele’s desire for privacy. This transition was aided by the introduction of timber mullion and transom windows with large panes of clear glass, the removal of awnings and the clearing of obstacles on the stoop. In addition, from the late eighteenth century there were technological innovations in interior lighting (Argand oil lamp and gas lamp), while the second half of the eighteenth century saw the emergence of the first ‘real’ shopfronts with accentuated entrances.With the relocation of the merchandise from the facade and the stoop to the shop space behind the facade, the furnishing of this space gained in importance. The sometimes exceedingly austere sixteenth- and seventeenth-century interiors, especially in the shops selling luxury goods on the main shopping streets, started to give way to interiors with beautifully decorated counters, cabinets and display cases. From the beginning of the nineteenth century, and once again influenced by London and Paris, the vital link with the public in the street was maintained via projecting shop windows and later by flat display windows and lavish lighting of the shop interior. At the same time, the first examples of the chain store made their appearance in Amsterdam.